(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
This article presents a comprehensive bibliometric analysis of global research trends in Technical and Vocational Education and Training (TVET) education. The study aims to identify key themes, prominent authors, influential journals, and geographic distribution of research in this field. Through systematic data collection and analysis of scholarly publications, including journal articles, conference papers, and books, this study provides insights into the evolution and current state of TVET education research worldwide. The analysis covers various topics within TVET, such as curriculum development, pedagogical approaches, industry partnerships, workforce development, and technology integration in education. By examining publication trends, this study reveals shifts in research focus and emerging areas of interest within the TVET education domain. The findings of this study can inform strategic initiatives for enhancing the quality and relevance of TVET education programs, fostering innovation and knowledge exchange, and addressing emerging challenges and opportunities in the global TVET landscape. This article underscores the importance of evidence-based research and data-driven insights in advancing TVET education globally.